Power Plant Tour: From Physical Field Trip to Virtual Reality (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
For engineering students, field trips to industrial facilities such as power plants provide invaluable hands-on experience in real-world settings. However, logistical constraints, safety concerns, restricted access, and financial limitations often prevent students from directly observing the operation of major equipment such as turbines, pumps, compressors, and heat exchangers. This study addresses these challenges by developing and evaluating a Virtual Reality (VR) application designed specifically for power plant education. As no pre-existing VR applications for power plant tours were available at the university, the system was developed from scratch. The VR creation process included scene planning, followed by the design of the virtual environment using specialized software such as Maya, Adobe Illustrator, Adobe Audition, and Unity3D. A pre- and post-survey study was conducted to evaluate the VR application’s effectiveness in enhancing learning outcomes. Participants were assessed on their understanding of power plant operations and overall experience with the VR tour. The results demonstrated that 65% of participants reported improved understanding of power plant operations, while 92% indicated they would recommend the VR experience to others. Additionally, 85% of participants rated the overall experience as good or excellent. These findings highlight the VR application’s potential to significantly enhance student engagement, improve comprehension of complex industrial systems, and provide a scalable, cost-effective alternative to traditional field trips. Overall, the study demonstrates the transformative potential of VR technology in engineering education. By addressing logistical and pedagogical challenges, VR offers an immersive and interactive platform for universities with limited access to industrial facilities. The results underscore VR’s effectiveness in bridging the gap between theoretical knowledge and practical application, paving the way for broader adoption in engineering and STEM curricula.